Tax Fraud on the Example of Issuing Fictitious VAT Invoices - Kobylski, Piotr (Journal of Finance and Financial Law, 2022)
The purpose of this article. In the literature, you can find quite extensive studies on value added tax, while the issue of tax fraud on the example of issuing fictitious VAT invoices from the perspective of the effect of Art. 56 § 1 of the Act of September 10, 1999 – Fiscal Penal Code has been treated quite fragmentarily. The main research objective of this study is to characterize the impact of the above-mentioned legal regulation in determining the scope of its impact on the tax law system. The work will prove that it is actually unjustified to maintain the current structure of the model of the right to deduct this tax. In connection with the above, the aim of the work will be to assess the directions of changes in the analyzed institution against the background of the applicable legal provisions. Methodology. It was created on the basis of an analysis of the content of legal acts and documents as well as studies of the subject literature. The result of the research. The taxpayer should not be held responsible for unlawful actions of third parties with regard to the fulfillment of the tax obligation in the tax on goods and services. Based on the considerations, it can be concluded that as long as the current structure of the model of the right to deduct tax on goods and services is maintained, this issue will still remain open.